Investigation of active site amino acid influence on carbon and chlorine isotope fractionation during reductive dechlorination. Issue 8 (14th June 2022) - Phillips, Elizabeth; Bulka, Olivia; Picott, Katherine; Kümmel, Steffen; Edwards, Elizabeth A; Nijenhuis, Ivonne; Gehre, Matthias; Dworatzek, Sandra; Webb, Jennifer; Sherwood Lollar, Barbara
Abstract: Reductive dehalogenases (RDases) are corrinoid-dependent enzymes that reductively dehalogenate organohalides in respiratory processes. By comparing isotope effects in biotically catalyzed reactions to reference experiments with abiotic corrinoid catalysts, compound-specific isotope analysis (CSIA) has been shown to yield valuable insights into enzyme mechanisms and kinetics, including RDases. Here, we report isotopic fractionation (ε) during biotransformation of chloroform (CF) for carbon (εC = -1.52 ± 0.34‰) and chlorine (εCl = -1.84 ± 0.19‰), corresponding to a ΛC/Cl value of 1.13 ± 0.35. These results are highly suppressed compared to isotope effects observed both during CF biotransformation by another organism with a highly similar RDase (>95% sequence identity) at the amino acid level, and to those observed during abiotic dehalogenation of CF. Amino acid differences occur at four locations within the two different RDases' active sites, and this study examines whether these differences potentially affect the observed εC, εCl, and ΛC/Cl . Structural protein models approximating the locations of the residues elucidate possible controls on reaction mechanisms and/or substrate binding efficiency. These four locations are not conserved among other chloroalkane reducing RDases with high amino acid similarity (>90%), suggesting that these locations may be important in determining isotope fractionation within this homologous group of RDases. Abstract : This study investigates the relationship between active site amino acid sequences with carbon and chlorine isotope fractionation for chlorinated alkane biotransformation by reductive dehalogenases..